Kinerja keuangan: profitabilitas dan solvabilitas pada PT Waskita Tbk periode 2017 – 2020 - Dwi Urip Wardoyo; Anastasia Adella Pashaningtyas Darmawan; Gumawang Giri Nugroho; Putri Wulan Dary; Yeni Jelita (Jurnal Riset Pendidikan Ekonomi, 2023)
The purpose of this study was to determine how influential the profitability ratios and solvency ratios of PT. Waskita Karya Tbk (WSKT) to the company's interim financial statements. The data collection method used in the research is using quantitative data including literature study, and analysis of company documents. The data collection technique uses purposive sampling as a particular consideration in determining the sample. Purposive sampling uses a quantitative approach so that the use of this technique is in accordance with research that will be carried out in the journal. The calculation of the solvency ratio uses the Debt toEquity Ratio (DER) and the Debt to Asset Ratio (DAR), while the calculation of the profitability ratio uses the Gross Profit Margin (GPM) and Return on Assets (ROA). The result from this research show that simultaneous profitability and solvability have no effect on financial performance of PT Waskita Karya Tbk 2017 – 2020 period. Based on parcially test profitability and solvability have no effect on financial performance of PT Waskita Karya Tbk 2017 – 2020 period.